Thermal behaviour of rebars and steel deck components of composite slabs under natural fire - Filho, Marcílio M. A. (2022)
Most of the studies involving composite slabs under fire follow the standard fire scenario described by the ISO 834 curve, disregarding the cooling-phase. However, recent studies show that this phase is equally important, as it can lead to the collapse of the structure. Therefore, the present research carried out a parametric study, using numerical models, validated through experimental tests, to evaluate the thermal behaviour of the composite slabs components under natural fire. The results showed that the maximum temperatures in the reinforcement bars occur during the cooling-phase, reaching temperatures up to 300% higher than at the heating-phase, on the steel deck occur at the end of heating, and that the concrete thickness above the steel deck influences the temperature of these components. Also, during the cooling-phase, a “heat bubble” effect is observed on the ribs of the composite slabs, where the reinforcement bars are normally placed. These results highlight the importance of considering different natural fire scenarios, in the structural performance and safety of composite slabs, since during the cooling-phase there is still heat transfer between the elements, which can lead to slab failure. New parameters are proposed to find the temperature of each component for different fire ratings.